Sliding Mode Tracking Control and GA-based Optimization for Reentry Guidance Subject to Multi-Constraints - Gu, Panfei; Qi, Ruiyun; Jiang, Bin (2018 IEEE CSAA Guidance, Navigation and Control Conference (CGNCC), 2018)
Considering the reentry guidance problem with multi-constraints of hypersonic gliding vehicle, this paper presents an improved guidance algorithm subjecting to multi-constraints, which is based on the sliding mode tracking control and genetic algorithm (GA). First, longitudinal guidance and lateral guidance were used to design the desired reentry guidance trajectory. Second, to improve the ability of robustness, sliding mode tracking control was proposed to track the desired trajectory. Besides, in order to guarantee that the tracking trajectory satisfied multi-constraints, the penalty function was applied into the cost function in the genetic algorithm to optimize parameters in the sliding mode surface. The numerical simulation was carried out in reentry guidance phase. The effect of the perturbations of the initial values and aerodynamic parameters was investigated. The result shows that guidance algorithm has the advantages of ensuring the actual reentry trajectory in the flight corridor and guidance commands in the boundary. It also has the advantage of high precision guidance and strong robustness to the perturbations.